2018
DOI: 10.1186/s12933-018-0727-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific associations between adolescent categories of BMI with cardiovascular and non-cardiovascular mortality in midlife

Abstract: ContextMost studies linking long-term consequences of adolescent underweight and obesity are limited to men.ObjectiveTo assess the sex-specific association of adolescent BMI with cardiovascular- and non-cardiovascular-related mortality in young adulthood and midlife.SettingA nationwide cohort.Participants927,868 women, 1,366,271 men.InterventionsMedical examination data at age 17, including BMI, were linked to the national death registry.Main outcomesDeath attributed to cardiovascular (CVD) and non-CVD causes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
0
13
1
Order By: Relevance
“…Obesity has become a major health problem worldwide and affects almost all of the major cardiovascular risk factors including hypertension, type-2 diabetes mellitus (T2DM), and hyperlipidemia [1][2][3][4][5]. Although obesity is associated with an increased risk of cardiovascular diseases (CVDs) and CVD-related risk factors [3], relevant epidemiologic studies have demonstrated obese or overweight T2DM patients may have better clinical outcomes compared with those at a normal weight [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has become a major health problem worldwide and affects almost all of the major cardiovascular risk factors including hypertension, type-2 diabetes mellitus (T2DM), and hyperlipidemia [1][2][3][4][5]. Although obesity is associated with an increased risk of cardiovascular diseases (CVDs) and CVD-related risk factors [3], relevant epidemiologic studies have demonstrated obese or overweight T2DM patients may have better clinical outcomes compared with those at a normal weight [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The TABS questionnaire was translated according to the guidelines for translating and adapting tests issued by the International Test Commission. 20 In addition to the questionnaire, demographic occupational details were reported by the participants. The details recorded were gender ('Males', 'Females' or 'Other'); birth country as an open-ended question; religious identification as 'Secular' or 'Religious'; seniority as 'Senior paediatrician' (a physician who passed the postgraduate examinations in paediatrics) or 'Resident' (a physician who is under postgraduate training in the field of paediatrics); and the location of their primary practice as 'Community clinic' or 'Hospital' (for senior physicians only).…”
Section: Methodsmentioning
confidence: 99%
“…BMI was calculated as weight (kg) divided by the squared height (m 2 ). A general physical examination was conducted by military physicians who also reviewed the participants’ medical records and recorded standard diagnostic codes when relevant [ 23 , 24 ]. Additional data regarding country of origin, education (divided into 4 categories: less than 9 years, 10 years, 11 years or 12 years) and residential SES were collected as detailed elsewhere [ 15 , 25 ].…”
Section: Methodsmentioning
confidence: 99%